Emotions in professional relations and employees’ health as exemplified by the teacher’s profession - Stadnyk, Magdalena; Szczygieł, Dorota; Książek, Janina (Polish Journal of Public Health, 2012)
Introduction. The teacher’s profession demands being in constant and intensive contact with other people, which entails a significant emotional strain and may, as a consequence, lead to health problems.Aim. The purpose of the study was to analyze the interrelations between the teachers’ health and the emotions they experience in contacts with students, and the ability to control the emotional states experienced.Material and methods. The study included 100 teachers, of whom 91 were women and 8 were men (one participant did not state the sex). Their health condition was examined by means of GHQ-12. The PANAS scale was used to evaluate positive and negative affectivity, and the INTE questionnaire to measure the emotional intelligence level. Declared emotions were measured using a questionnaire developed for the purposes of this paper.Results. The relationship between negative emotions and health was found during the control of seniority and dispositional variables: positive and negative affectivity and emotional intelligence. The level of health disorders in the examined teachers negatively correlates with emotional intelligence (r=-0.43, p